2022
DOI: 10.3390/jpm12071151
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Strategy to Decrease the Revision Rate of Fassier–Duval Nailing in the Lower Limbs of Osteogenesis Imperfecta

Abstract: (1) Background: The Fassier–Duval (FD) nail was developed for the treatment of osteogenesis imperfecta (OI). The aim of this study was to review the results of OI patients treated with the FD nail at our institution and discuss a surgical strategy to decrease the FD nail revision rate; (2) Methods: We retrospectively reviewed OI patients treated at our institution between 2015 and 2020. OI patients treated with FD nail insertion in the long bones of the lower extremities were included, and those with a follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
(35 reference statements)
1
5
0
Order By: Relevance
“…In this study, one third of patients who received a telescopic rod required revision surgery during the follow-up period. This is slightly improved from previous studies that showed 53% to 58% revision rates 12,15,16…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…In this study, one third of patients who received a telescopic rod required revision surgery during the follow-up period. This is slightly improved from previous studies that showed 53% to 58% revision rates 12,15,16…”
Section: Discussionsupporting
confidence: 53%
“…This is slightly improved from previous studies that showed 53% to 58% revision rates. 12,15,16 In our study, bent implants were an indication for revision in nearly half of the revision cases (48.2%), making it the most frequent reason for revision. This is different from the series reported by Musielak et al 17 who found that the migration of the male component was the most common indication for revision, accounting for 45% of revisions, with bent rods accounting for 8.6% of revisions.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Common reasons for implant failure in the femur include bending and female component migration. The average interval between previous FD nail insertion and revision surgery was 2.4 years [ 8 ]. Taking this into consideration, we can reasonably conclude that the female component migration in the left femur experienced by the patient in this study is not an unforeseen complication that may require reoperation in the future.…”
Section: Discussionmentioning
confidence: 99%